2008
DOI: 10.1302/0301-620x.90b9.20056
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-induced osteonecrosis

Abstract: Severe acute respiratory syndrome (SARS) is a newly described infectious disease caused by the SARS coronavirus which attacks the immune system and pulmonary epithelium. It is treated with regular high doses of corticosteroids. Our aim was to determine the relationship between the dosage of steroids and the number and distribution of osteonecrotic lesions in patients treated with steroids during the SARS epidemic in Beijing, China in 2003. We identified 114 patients for inclusion in the study. Of these, 43 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 17 publications
1
23
1
2
Order By: Relevance
“…At the time of initial treatment, the patient’s hip fracture was thought to be due to her long-standing osteoporosis from high-dose corticosteroid use for the treatment of her ulcerative colitis. Long-term use of steroids leading to osteoporosis and increased risk of fractures has been well documented in the literature [5-7]. Gasterointestinal diseases in childhood have also been implicated as a cause of osteoporosis [8].…”
Section: Discussionmentioning
confidence: 99%
“…At the time of initial treatment, the patient’s hip fracture was thought to be due to her long-standing osteoporosis from high-dose corticosteroid use for the treatment of her ulcerative colitis. Long-term use of steroids leading to osteoporosis and increased risk of fractures has been well documented in the literature [5-7]. Gasterointestinal diseases in childhood have also been implicated as a cause of osteoporosis [8].…”
Section: Discussionmentioning
confidence: 99%
“…In another study on 540 SLE patients, mean daily dose and intravenous pulse in addition to cumulative dose of prednisolone were related to ON ( 12 ). Zhang et al showed that the number of ON lesions was directly associated with the dosage of CS, pulse and cumulative regimen ( 13 ). In other survey on 106 SLE patients during follow up period of 13.6 years, total duration of CS and duration of treatment was not related to ON ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…A particularly devastating cause is steroid use, which may result in fat and/or thromboembolism and compromise the blood supply to the femoral head [ 1 ]. However, little is understood about the duration and quantity of steroids required to cause osteonecrosis [ 5 - 7 ].…”
Section: Introductionmentioning
confidence: 99%